A Qualitative Report of Sport Facilities Management - Wondemagnegn A; Zemikael G (CV. Publikasi Indonesia, 2023)
This qualitative report aims to explore the management of sports facilities from the perspective of facility managers. The study utilizes a qualitative research approach and specific interviews with five facility managers from various sports facilities. The interviews were analyzed using thematic analysis to identify common themes and patterns in the managers' responses. The findings of this study suggest that effective management of sports facilities requires a multidisciplinary approach, involving aspects of business, marketing, and facility operations. The managers identified key challenges in managing sports facilities, such as limited funding, maintenance issues, and changing technology. The study also highlighted the importance of effective communication between facility managers, staff, and stakeholders in maintaining and improving sports facilities. The study contributes to the growing body of literature on sports facility management by providing insight into the perspectives and experiences of facility managers. The findings can inform future research and assist in developing strategies for improving the management of sports facilities. Ultimately, this report aims to promote effective management practices that enhance the user experience and promote the value of sports facilities in the community.